Continuous maps in terms of new convergence conditions - Gupta, Asha (Global Journal of Mathematical Analysis, 2014)
It is well known that if X is Frechet, then a map f : X –>Y is continuous if and only if xn –> x in X implies f(xn)–> f(x) in Y . In this paper, some new convergence conditions in terms of sequences have been introduced and in terms of these convergence conditions, generalisations and analogues of some known results of continuous maps are obtained. Keywords: Convergence, continuous, Frechet , Sequence.